Online Learning Implementation and Challenges; Case in rural and urban schools in Sintang District - Dedi Irwan (IKIP PGRI Pontianak, 2020)
This research aimed to describe online learning implementation and challenges carried out by rural and urban schools during Covid-19 pandemic in Sintang District. A descriptive qualitative approach was adopted in order to collect deep data which was rich of contextual detail regarding how online learning had been implemented in each school and what challenges they faced in order to implement online learning optimally. Four schools representing rural and urban areas were involved in this research. In this regard, rural and urban areas were represented by two schools each. Within each school, five respondents were involved, a school leader, two teachers and two students. In total, this research involved 20 respondents. Data collection process were carried out using semi structured interview, assisted by an interview guidance. To analyse the data, this research adopted thematic analysis and cross-case analysis. The finding of this research suggested that there was variation in the way rural and urban schools implemented online learning during covid 19 pandemic. Furthermore, the data analysis also revealed a number of challenges faced by rural and urban school in implementing the online learning. Overall, rural schools mostly dealt with limited supporting online learning facilities, meanwhile, urban schools demanded further assistances on improving their readiness to embrace online learning in their schools.